Dynamics of Administrative Law, Financial Law, and Government Accountability - Muhammad Dzul Ikram; Marta Satria Putra; Abdul Latif (International Journal Labs, 2025)
The study of administrative and financial law in Indonesia has rapidly evolved, driven by the democratization process and the government's focus on financial governance. Administrative law regulates the relationship between the government and citizens, overseeing decision-making and the implementation of government functions, while financial law manages state finances, including taxes and budgets, adapting to societal and technological changes. Both branches impose responsibilities: administrative duties involve public service and governance, whereas financial responsibilities focus on managing state finances and ensuring legal certainty, with an emphasis on integrity and accountability. However, challenges persist, such as decision-making failures, procedural violations, corruption, bureaucratic delays, and inadequate public services in administrative law, alongside issues like poor budget planning and mismanagement in financial law. This study employs normative and empirical legal analyses to examine these challenges and their implications for contemporary governance, aiming to enhance understanding of both branches of law, analyze their impact on government actions, improve oversight of state finances, and bolster accountability for efficient financial management, ultimately benefiting the public.